Framework Administered Account for Selected Fund Activities : European Investment Bank Subaccount for Selected Fund Activities. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The Fund, represented by the Managing Director, has reached understandings with the EIB to finance capacity building (technical assistance and training) and related activities. On the basis of these understandings, the Managing Director has established the essential terms and conditions of the Subaccount, with which EIB concurs, with respect to the nature, design, and implementation of the activities to be financed and the method by which the costs of the activities will be financed from the Subaccount.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet